Nurses' Performance Based on Performance Determinants in Several Type C Hospitals: A Comparative Study - Lina Maesaroh; Muhammad Hadi; Melati Fajarini; Fitri Arofiati; Tini Suminarti (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: This research is motivated by data on nurse performance and data on nurses resigning in 2020 and 2021 increasing every year in Type C Hospitals, the determinant of performance is an assessment that can affect the performance of nurses. Objectives: To determine the performance of nurses based on performance determinants in several type C hospitals. Methods: This comparative study was conducted on nurses at Mekar Sari Hospital, Cilincing Regional General Hospital and Dik Pusdikkes Hospital TNI AD totaling 96 respondents in May 2022 and randomly selected based on the inclusion criteria. The performance questionnaire as many as 41 questions and the performance determinant questionnaire as many as 36 questions, were given directly to nurses to get an overview of performance. Data were analyzed using Multiple Logistics Regression. Results: Nurse performance at Mekar Sari Hospital was 78.9%, Cilincing Hospital was 96.4% and Dik Pusdikkes Hospital was 70.0%. There is a difference in the description of the performance of nurses at Mekar Sari Hospital, Dik Pusdikkes Hospital with Cilincing Regional General Hospital with P < 0.05, There is no difference in the description of the performance of nurses at Mekar Sari Hospital and Dik Pusdikkes Hospital with P > 0, 05. Motivation, work ability, compensation and tenure are the most dominant factors influencing performance in several type C hospitals. Conclusion: The performance of nurses at Cilincing Hospital is higher than the performance of nurses at Mekar Sari Hospital and Dik Pusdikkes Hospital. Motivation, work ability, compensation and tenure affect performance. Keywords: Nurse Performance, Performance Determinants, Performance Appraisal